2019
DOI: 10.1038/s41558-019-0553-2
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of anthropogenic signals in the ocean carbon cycle

Abstract: Attribution of anthropogenically-forced trends in the climate system requires understanding when and how such signals will emerge from natural variability. We apply time-of-emergence diagnostics to a Large Ensemble of an Earth System Model, providing both a conceptual framework for interpreting the detectability of anthropogenic impacts in the ocean carbon cycle and observational sampling strategies required to achieve detection. We find emergence timescales ranging from under a decade to over a century, a con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
77
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 77 publications
(90 citation statements)
references
References 57 publications
(61 reference statements)
12
77
1
Order By: Relevance
“…The predictability time horizon of surface pH is mainly determined by a complex interplay between DIC and Alk predictability in the low latitudes and DIC, Alk and temperature predictability in high latitudes. Interestingly, we find longer predictability time horizons for SST than for NPP in the equatorial Pacific, which is in contrast to findings of Séférian et al (2014a). Importantly, this may be indicative of a potential model dependency of the relationship between ecosystem driver predictability.…”
Section: Discussioncontrasting
confidence: 90%
See 3 more Smart Citations
“…The predictability time horizon of surface pH is mainly determined by a complex interplay between DIC and Alk predictability in the low latitudes and DIC, Alk and temperature predictability in high latitudes. Interestingly, we find longer predictability time horizons for SST than for NPP in the equatorial Pacific, which is in contrast to findings of Séférian et al (2014a). Importantly, this may be indicative of a potential model dependency of the relationship between ecosystem driver predictability.…”
Section: Discussioncontrasting
confidence: 90%
“…Our results suggesting the same global predictability time horizon for all four ecosystem drivers are not inconsistent with time of emergence diagnostics for transient climate warming scenarios where pH (early emergence) and NPP (late emergence) behave oppositely (Frölicher et al, 2016;Rodgers et al, 2015;Schlunegger et al, 2019). Time of emergence is defined as the ratio (large for pH and small for NPP) of the anthropogenic forced change to the background internal variability.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…The answer may have implications for measurement strategies to detect anthropogenic changes in subsurface waters as well as for the impacts of physical and biogeochemical change on marine life. For the surface ocean, earlier studies (Keller et al, 2014;Rodgers et al, 2015;Frölicher et al, 2016;Schlunegger et al, 2019) showed that the anthropogenic signals of pH and pCO 2 emerge earlier than sea surface temperature and O 2 change earlier than productivity. Changes in surface O 2 are tightly coupled to temperature-driven solubility changes and O 2 varies hand in hand with sea surface temperature and the two signals emerge typically concomitantly.…”
Section: Introductionmentioning
confidence: 99%